Implementation of Character Education in Social Studies Subjects at the Special School D / D1 YPAC Semarang - Muryanti, Sri; Masrukhi, Masrukhi; Pramono, Suwito Eko (Universitas Negeri Semarang, 2020)
Social studies have an essential role in applying character values ​​for students. The purpose of social studies is to form good character and prepare students to become good citizens. This is following the goals of character education for children with special needs, namely to meet needs, familiarize social life, and form good behavior and attitudes following the norms prevailing in the society. Therefore, students must live in harmony with the community, and so must be applied in students. So that the problems in the form of a lack of independent nature and self-confidence of SLB students at YPAC Semarang are problems that must be resolved by teachers and schools as facilitators, a low character of student discipline accompanies this lack of attitude, so schools need to implement it. For SMPLB D / D1 YPAC Semarang, character internalization that is trying to be carried out includes the value of the self-confident character to find their potential and develop according to their talents. Have an independent nature to equipping children with special needs to live independently by minimizing assistance from other parties and the character of discipline that will later become provisions before living in society.